Supporting Factors Faced By Students In Learning English In The New Normal Era - Novayanti Sopia Rukmana; Geminastiti Sakkir; Ahmad Bukhori Muslim; Martin Andrew (Seminar Nasional LP2M UNM, 2022)
Abstract. This article was a part of the research with the title ”Students' English Learning Strategies in the New Normal Era”. The research method was the qualitative descriptive design. This research was used to determine the supporting factors faced by students in learning English in the new normal era. The subjects that will be involved are students in SMA/MA/SMK/equivalent in South Sulawesi Province. The data was obtained from the questionnaire. The qualitative data were analyzed through qualitative data analysis techniques consisting of data reduction, data display, and conclusion drawing/verification. The results of the analysis will be in the form of a description of the supporting factors faced in learning English in the New Normal period. This description will be useful for learners, teachers, policymakers, and theorists of education and foreign language learning. This research is related to the implementation of students' English learning strategies in the new normal era. The researcher distributed the questionnaire on the Google Form link to several high school students in South Sulawesi and 206 students sent back the results. The results of the study showed that many supporting factors faced by students in learning English during the current New Normal (before the Pandemic, during and after the Covid-19 Pandemic). These factors and challenges come from student conditions, teacher conditions, school conditions, environmental conditions, material conditions, learning processes, administrative processes, and the application of technology. Keywords: Factors, Learning, Strategies, New Normal.